1975
DOI: 10.1152/jn.1975.38.4.922
|View full text |Cite
|
Sign up to set email alerts
|

Neural repetitive firing: a comparative study of membrane properties of crustacean walking leg axons

Abstract: 1. Repetitive activity and membrane conductance parameters of crab walking leg axons have been studied in the double sucrose gap. 2. The responses to constant current stimulus could be classified into three catagories; highly repetitive with wide firing frequency range, type I; highly repetitive with narrow frequency range, type II; and nonrepetitive or repetitive to only a limited degree, type III. The minimum firing frequency for type I axons was much greater than for other recording techniques. 3. Voltage-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
47
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 0 publications
7
47
0
Order By: Relevance
“…The strong anti-Shaker staining observed in the distal membranes of most axons suggests that Shaker channels contribute to spike propagation in pyloric neurons, as is true for Shaker channels in a variety of species (Wang et al, 1993;Rosenthal et al, 1996Rosenthal et al, , 1997Rogero et al, 1997). This observation is consistent with the fact that both sustained and transient K ϩ currents exist in lobster axons (Connor, 1975). Interestingly, Shaker channel distribution is not uniform along an axon, and Shaker channels are missing from the proximal regions.…”
Section: Shaker and Shal Contribute To Distinct Firing Properties Witsupporting
confidence: 60%
“…The strong anti-Shaker staining observed in the distal membranes of most axons suggests that Shaker channels contribute to spike propagation in pyloric neurons, as is true for Shaker channels in a variety of species (Wang et al, 1993;Rosenthal et al, 1996Rosenthal et al, , 1997Rogero et al, 1997). This observation is consistent with the fact that both sustained and transient K ϩ currents exist in lobster axons (Connor, 1975). Interestingly, Shaker channel distribution is not uniform along an axon, and Shaker channels are missing from the proximal regions.…”
Section: Shaker and Shal Contribute To Distinct Firing Properties Witsupporting
confidence: 60%
“…Activation of 'A opposes depolarization and lengthens the time to the threshold of spike. It has been concluded that a frequency-encoding function in these cells is attributable to these characteristics of IA (Connor, 1975(Connor, , 1980. On the other hand, 'A-like current in cardiac cells has been reported as a current responsible for the early repolarization of action potentials (Josephson et al 1984;Giles & van Ginneken, 1985;.…”
Section: Effects Of Divalent Cations On Itomentioning
confidence: 99%
“…Experimentally, this means the frequency-input current (or FI) curve has a specific shape, called Type I, such that firing frequency smoothly approaches zero at current threshold (1-6). By contrast, so-called Type II neurons have a lower bound in their firing frequency and move abruptly from quiescence to fast spiking, with this transition visible as a sharp jump in the FI curve at threshold (1,3,5).Type I behavior is physiologically unlikely with a minimal set of membrane currents such as the voltage-gated sodium and delayed-rectifier potassium currents in the standard squid giant axon Hodgkin-Huxley model, which is Type II. Classic experimental (1, 7) and theoretical studies (3-5, 8, 9) revealed that a Type II membrane (such as a squid giant axon) can be turned into a Type I membrane by adding an inactivating (A-type) potassium conductance, I A .…”
mentioning
confidence: 99%
“…For a neuron to represent continuously varying signals in its firing rate, it must be able to fire at low, high, and all intermediate frequencies. Experimentally, this means the frequency-input current (or FI) curve has a specific shape, called Type I, such that firing frequency smoothly approaches zero at current threshold (1)(2)(3)(4)(5)(6). By contrast, so-called Type II neurons have a lower bound in their firing frequency and move abruptly from quiescence to fast spiking, with this transition visible as a sharp jump in the FI curve at threshold (1,3,5).…”
mentioning
confidence: 99%
See 1 more Smart Citation